Conceive-Design-Implement-Operate (CDIO) Approach for an Innovative Capstone Project - Jambari, Hanifah; Razali, Nurul Amalin; Taman, Ishak; Noh@Seth, Nur Hazirah; Osman, Sharifah; Ahmad, Jamilah; Mohamad Nordin, Norjulia; Mohd Rameli, & Mohd Rustam (Journal of Technical Education and Training, 2018)
The development of engineering education plays an important role in promoting a comprehensive national strength due to the scientific innovation results in great changes of industry structure. Therefore, conceive-design-implement-operate (CDIO) approach recognises that the engineering education can be acquired from a variety of institutions and the educators in all parts of this spectrum can learn the practice elsewhere. Thus, the purpose of this study is to identify the students and lecturers’ perceptions on the CDIO approaches in a capstone project in two faculties, namely Faculty of Biosciences & Medical Engineering (FBME) and Faculty of Electrical Engineering (FKE) at Universiti Teknologi Malaysia (UTM). The respondents were five lecturers each from FBME and FKE who were directly involved with the capstone project and 28 and 30 third-year students from FBME and FKE respectively. The 5-point Likert scale questionnaires used had been validated by an expert panel with adequate reliability. The data analysis results indicate that the students and lecturers have positive perceptions of the CDIO approaches when used in the capstone project. Thus, the approach can be successfully implemented in an undergraduate engineering programme to enhance their technical skill particularly to produce creative and innovative project which is in line with current technology.